Functional foods in the prevention of periodontal disease (Research, Society and Development, 2020)
Introduction: Periodontal disease is caused by changes in the oral microbiota (increase or decrease in specific colonies) and results in the degradation of the oral tissues that protect and support the teeth, called periodontal support and protective tissues. The interest of industries and the population for functional foods is increasing in the search for the prevention of periodontal diseases. Objective: To describe, from a literature review, how the use of functional foods influences the prevention of periodontal diseases. Methodology: The article was developed from an exploratory review of articles selected in the Scielo, Google Scholar and PubMed database platforms. Results: The authors of the selected articles demonstrated that consuming functional foods that contain vitamins, probiotics, isoflavones and polyphenols, within nutritional balance, are beneficial alternatives in preventing periodontal disease. Conclusion: Functional foods prevent periodontal disease by mechanisms related to its anti-inflammatory, immunostimulating and antimicrobial activities.